Eksistensi Marsiadapari dan Relevansinya dengan Teori Solidaritas di Desa Batumanumpak Kecamatan Pangaribuan Kabupaten Tapanuli Utara Tahun 2023 - Elisabeth Harianja; Rusmauli Simbolon; Harisan Boni Firmando; Masniar Hernawaty Sitorus; Tio RJ Nadeak (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This research aims to determine the existence of marsiadapari and its relevance to solidarity theory in Batumanumpak Village, Pangaribuan District, North Tapanuli Regency in 2023. This research uses qualitative research methods, to gain an understanding of social or human problems conducted in a natural research setting. Data collection in this research used observation, interview and documentation techniques. The results of this research show that the existence of the local wisdom culture of marsiadapari is a local wisdom of the Toba Batak community which still exists from ancient times to sekran in Batumanumpak Village. marsiadapari is a system of mutual cooperation carried out by a group of people in an activity or job. This work is carried out by a group of people in agricultural land work activities. In the midst of the sophistication of the times, marsiadapari has not been abandoned and forgotten by the people of Batumanumpak Village, even though its implementation is not completely carried out as traditionally as before. The reason marsiadapari is still carried out is because marsiadapari is a legacy of local wisdom from ancestors that must be preserved and a tool to increase solidarity, tolerance and togetherness and also save costs for the people of Batumanumpak Village. Marsiadapari activities contain moral values ​​that are firmly held by the people of Batumanumpak Village and are believed to be a guide to a good life for the people of Batumanumpak Village.